Development of Computer Assisted Instruction as a Means of Independent Learning - Septriyan Anugrah; Ambiyar Ambiyar; Giatman Giatman; Rindang Ayu; Syintia Fareara (AT-TA'LIM, 2022)
The development of Science, Technology, and Arts (IPTEKS) which so rapidly affects the process of implementing education can no longer be done conventionally. The learning methodology needs to adapt to these technological developments so that it can be carried out efficiently and effectively. This challenges education experts to continue to innovate in developing learning methods and strategies. How the learning process is carried out in a short time, and not always face to face between the lecturers and students but get the results as expected. One alternative to overcome this problem is to utilize computer-assisted instruction (CAI). This study aims to develop multi-media computer-assisted instruction (CAI) as a means of independent learning. This study uses the Multimedia Development Life Cycle method by Luther (1994), which includes six stages of development, namely concept (concept), design (design), material collection, assembly (manufacture), testing (testing), and distribution (distribution). At the testing stage, an alpha (alpha test) was carried out by the experts, while at the distribution stage the students were tested with indicators of usability, ease of use, ease of learning, and satisfaction. Conclusion for all aspects of the overall validity, practicability, and feasibility test, it can be ignored that multi-media computer-assisted instruction (CAI) is valid, practical, and worthy of being used as a means of independent learning